PENGARUH UKURAN PERUSAHAAN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019-2021 - Dia Agustin; Dwi Lesno Panglipursari (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine and analyze the effect of Company Size and Debt Policy on Firm Value in Property and Real Estate sector companies listed on the IDX for the 2019-2021 period. The population in this study were 43 companies. The sampling technique in this study used a purposive sampling technique, namely a sampling technique based on certain criteria. The number of samples in this study were 43 companies with 3 years of research so that the sample data in this study totaled 129 data. Methods of data analysis using descriptive statistics, classical assumption test, multiple linear regression analysis, and hypothesis testing. Based on the results of this study indicate that partially company size as measured by Size has no significant effect on firm value, debt policy as measured by Debt to Equity Ratio (DER) has a negative and significant effect on firm value. Meanwhile, it simultaneously shows that company size and debt policy have a significant effect on firm value.